Determination of undrained strengths by cone penetration tests. - Houlsby, G; Wroth, C (Balkema, 1982)
Calculations have been presented for the loads on a cone penetrometer in a cohesive material, with the validity of the calculations being limited at present to a penetrometer near the surface of a soil. The undrained strength of a cohesive soil could therefore be back-analysed from measurements of loads on cone penetrometers. -from Authors